Application Analysis of Artificial Intelligence in Power System Fault Diagnosis - Jinbiao, Dou (Journal of Theory and Practice of Management Science, 2025)
In the current development situation, the power industry has become one of the important factors affecting China's social and economic development and the quality of life of the people, and has significant implications for the development of China's social and economic development. In this situation, the demand for electricity in various regions of China is rapidly increasing, and the power system is also under high operating pressure, leading to frequent incidents such as transformer failures and transmission line failures. This not only has a serious impact on the economic development of various regions, but also brings many inconveniences to people's lives. However, many facilities and equipment in the power system are relatively sophisticated, and it is impossible to accurately determine the type and cause of faults solely based on the inspection of staff. The emergence of artificial intelligence technology provides necessary technical support for the diagnosis of power system faults, which can help workers find and solve related faults in a relatively short period of time. Based on this, this article focuses on the application of artificial intelligence in power system fault diagnosis, and further promotes the healthy and stable development of China's power industry.